Το πορτρέτο του συγγραφέα μπροστά στον φακό. Βιογραφικά ντοκιμαντέρ λογοτεχνών στον κινηματογράφο και στην τηλεόραση την περίοδο της Μεταπολίτευσης (1980-1990) - Ζησιμοπούλου, Σοφία (Σύγκριση/Comparaison/Comparison, 2023)
The portrait of the author in front of the camera lens. Biographical documentaries of litterateurs in cinema and television in the Regime change period (1980-1990) In this paper, I discuss the ways in which biographical documentaries established a new paradigm of approaching writers’ lives and literary texts during the 1980s-1990s in Greece. Despite their heterogeneous topics and stylistic characteristics, these documentaries display similar narrative patterns and strategies for presenting each authorial persona. Focusing on a representative sample of films, I attempt to analyze some of these patterns and strategies. More specifically I map the terms of the writers’ participation in several documentary films and their involvement in the construction of a specific public identity through the process of filmmaking. At the same time, I focus on the narrative dynamics of photographic documents and oral testimonies. Finally, I highlight the importance of these documentary films for the comprehension of the writers’ reception both in a synchronic and diachronic horizon. The main argument of my paper is that these documentary films accomplish to go beyond the limits of a single biography and represent many versions of a shared past.